Do the KIND Thing : THINK Boundlessly WORK Purposefully Live Passioantely - Lubetzky, Daniel
The Founder and CEO of the KIND brand of healthy snacks shares the story of his childhood in Mexico as the son of a Holocaust survivor and his professional successes, outlining his philosophies about business practices that combine profit goals and so